2011
DOI: 10.1074/jbc.m110.183608
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insight into the Differential Effects of Omega-3 and Omega-6 Fatty Acids on the Production of Aβ Peptides and Amyloid Plaques

Abstract: Several studies have shown the protective effects of dietary enrichment of various lipids in several late-onset animal models of Alzheimer Disease (AD); however, none of the studies has determined which structure within a lipid determines its detrimental or beneficial effects on AD. High-sensitivity enzyme-linked immunosorbent assay (ELISA) shows that saturated fatty acids (SFAs), upstream omega-3 FAs, and arachidonic acid (AA) resulted in significantly higher secretion of both A␤ 40 and 42 peptides compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 48 publications
(40 reference statements)
1
25
2
Order By: Relevance
“…At least one ω6-PUFA oxidation product is amyloidogenic while its corresponding ω3-PUFA oxidation product is not [27], suggesting that dietary ω3-PUFA deficiency may render brain tissue more vulnerable to amyloidogenic effects of oxidative stress by increasing the production of ω6-PUFA oxidation products [41,48]. Conversely, dietary DHA supplementation alleviates the histopathological signs of Alzheimer’s disease in mice, and in neuronal cell cultures [33,4955]. Therefore, the development of amyloid in brain may depend to some extent on the degree to which ω6-PUFAs such as DPA displace ω3-PUFAs such as DHA in a pool that is vulnerable to oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…At least one ω6-PUFA oxidation product is amyloidogenic while its corresponding ω3-PUFA oxidation product is not [27], suggesting that dietary ω3-PUFA deficiency may render brain tissue more vulnerable to amyloidogenic effects of oxidative stress by increasing the production of ω6-PUFA oxidation products [41,48]. Conversely, dietary DHA supplementation alleviates the histopathological signs of Alzheimer’s disease in mice, and in neuronal cell cultures [33,4955]. Therefore, the development of amyloid in brain may depend to some extent on the degree to which ω6-PUFAs such as DPA displace ω3-PUFAs such as DHA in a pool that is vulnerable to oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were corroborated in vivo by using a transgenic mouse model of early-onset Alzheimer’s disease that expresses the double-mutant form of human APP, which is the precursor protein responsible for the synthesis of Aβ peptide. Decreased levels of Aβ peptide and less accumulation in the form of amyloid plaques were observed in the brain of mice nourished with a diet enriched in n-3 PUFAs, mainly DHA (22:6 n-3; Amtul et al, 2011a). Not only extraneously supplied but endogenously synthesized n-3 PUFAs can suppress the synthesis of Aβ peptide and the formation of amyloid plaques.…”
Section: Evidence Of the Importance Of Fatty Acids For Health And Dismentioning
confidence: 99%
“…Using APP-C99-transfected COS-7 cells, a cellular model of Alzheimer’s disease-like degeneration, a study was carried out to investigate the class of fatty acids that was thought to influence the production of Aβ peptide, which is a major neuropathological hallmark of disease. It was shown that palmitic acid (16:0), stearic acid (18:0), upstream n-3 PUFAs, and AA (20:4 n-6) triggered higher secretion of Aβ peptide compared to long chain downstream n-3 PUFAs and MUFAs (Amtul et al, 2011a). These findings were corroborated in vivo by using a transgenic mouse model of early-onset Alzheimer’s disease that expresses the double-mutant form of human APP, which is the precursor protein responsible for the synthesis of Aβ peptide.…”
Section: Evidence Of the Importance Of Fatty Acids For Health And Dismentioning
confidence: 99%
“…Importantly, omega-3 acids have shown the ability to inhibit tau hyperphosphorylation,29 which would allow axonal transport restoration. It has been shown that omega-3 is also capable of reducing amyloid plaque formation 29,30…”
Section: Neuronal Restoration In Ad Patientsmentioning
confidence: 99%